1994
DOI: 10.1021/jm00027a001
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of novel cyclic RGD-containing peptides as highly potent and selective integrin .alpha.IIb.beta.3 antagonists

Abstract: Utilizing conformational constraints in conjunction with various structural considerations, we have synthesized a series of cyclic disulfide peptides that are highly potent and selective antagonists for the platelet integrin alpha IIb beta 3 (GPIIb/IIIa). The affinities of the peptides for alpha IIb beta 3 were determined by platelet aggregation assays and an alpha IIb beta 3 ELISA. Their affinities for alpha 5 beta 1 and alpha v beta 5 integrins were also determined in respective ELISA assays. Structure-activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(117 citation statements)
references
References 17 publications
3
113
0
1
Order By: Relevance
“…The soluble proteins were used to inhibit platelet aggregation. IC 50 s were 0.6 Ϯ 0.2 and 2.1 Ϯ 0.4 M for MalE-RGD and MalE-EETI-CK RGD , respectively, which are close to the IC 50 of 0.33 M obtained for the cyclic CIPRGDYRC (8). No inhibition of platelet aggregation was observed with MalE-EETI-II (data not shown).…”
Section: Vol 183 2001 E Coli K-12 Surface Display Of Ehec Intimin supporting
confidence: 75%
See 2 more Smart Citations
“…The soluble proteins were used to inhibit platelet aggregation. IC 50 s were 0.6 Ϯ 0.2 and 2.1 Ϯ 0.4 M for MalE-RGD and MalE-EETI-CK RGD , respectively, which are close to the IC 50 of 0.33 M obtained for the cyclic CIPRGDYRC (8). No inhibition of platelet aggregation was observed with MalE-EETI-II (data not shown).…”
Section: Vol 183 2001 E Coli K-12 Surface Display Of Ehec Intimin supporting
confidence: 75%
“…Aggregation was stimulated by adding 25 M ADP, and the change in OD 650 was monitored by photometry. Values were expressed as percent aggregation, which represents the percentage of light transmission standardized to fully and not aggregated samples (8). The IC 50 is the concentration of the protein at which the platelet aggregation is inhibited by 50%.…”
Section: Flow-cytometric Analysis and Facsmentioning
confidence: 99%
See 1 more Smart Citation
“…The a v h 3 integrin is one of the most specific biomarkers that can differentiate newly formed capillaries from their mature counterparts (67). High-affinity a v h 3 -selective ligands, Arg-Gly-Asp (RGD) in its conformationally constrained cyclic form has a higher binding affinity than in its linear form (68). Ternary doxorubicin-loaded poly(ethylene glycol) nanoparticles conjugated to cyclic RGD (69) and paclitaxel-cyclic RGD nanoparticles have recently been reported.…”
Section: Characteristics Of Cell Surface Receptors and Antigensmentioning
confidence: 99%
“…It has been previously shown that cells adhere to cycloRGD significantly more strongly (10 times) than to the linearized form. 55 The VnRGD peptide was derived from the fulllength vitronectin protein sequence, containing the RGD sequence 56 based on work done previously. 57 To investigate the adhesive properties of each RGD peptide on ASCs, we performed 3 h-long adhesion assays.…”
Section: Clevenger Et Almentioning
confidence: 99%